Development of Volleyball Lower Passing Module Web Based on Junior High School Students - Sandy Yudha Sinurat; Nimrot Manalu; Nurhayati Simatupang; Indra Kasih (Randwick International of Education and Linguistics Science Journal, 2022)
This study aims to see the results of web-based developed products regarding the lower passing of volleyball at SMP Negeri 1 Pantai labu. Type. Assessment from material experts 92.6%, from website media experts 88.3% with excellent criteria Assessment from Linguists 88.3% with excellent criteria In the pretest and postest tests conducted in classes VIII- G and VIII-B obtained a score of 64.28% in the pretest class. in the posttest class it gained 83% with a difference of 18.72%. From the trial, an increase in interest in learning was obtained, meaning that website-based learning has a positive impact on student learning outcomes even though learning is still online or 50% face-to-face learning. Overall the assessment of the quality of the product is "very worthy" to use.